Saint young men. 5 - Nakamura, Hikaru, 1984- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2021)
"Buddha, the Enlightened One, and Jesus, Son of God, continue their extended vacation in the mortal realm. With a little help from their neighbors and the incessant meddling of their heavenly pals, the saintly duo explores new sights and experiences of daily life in Japan, from family restaurants to sports to manga--with wisecracks aplenty!"--Back cover.